Energy cost of middle distance running races - Hill, D. W. (Medicine & Science in Sports & Exercise, 1995)
Estimates of the energy contributions to performing three middle distance races were obtained by combining both laboratory and field measurements on Ss in multiple races. The estimates were: Distance % anaerobic % aerobic 400 m 68 +- 6% 32 +- 6% 800 m 42 +- 5% 58 +- 5% 1500 m 20 +- 4% 80 +- 4% Implication: These estimates are similar to those for swimming and kayak races of a like duration. It would appear for 800 m races and longer that aerobic training will be a greater determinant of success than anaerobic (sprint) training because aerobic energy makes the dominant contribution.